Fungal diversity associated with anthracnose in chili peppers of West Sumatra, Indonesia, using conventional and NGS approaches - RIKI WARMAN; HALIATUR RAHMA; DARNETTY DARNETTY; RITA NOVERIZA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Warman R, Rahma H, Darnetty, Noveriza R. 2025. Fungal diversity associated with anthracnose in chili peppers of West Sumatra, Indonesia, using conventional and NGS approaches. Biodiversitas 26: 4257-4266. Curly red chili plants are one of the leading horticultural commodities in West Sumatra, Indonesia. However, there has been a 90% decline in yield due to anthracnose disease. Anthracnose is caused by various fungi from the Colletotrichum genus and other fungi that interact within it. The objective of this study is to compare the diversity of fungi associated with anthracnose disease symptoms in West Sumatra using NGS (Next-Generation Sequencing) and conventional identification techniques. This study used a field survey method involving the collection of chili fruit samples with anthracnose symptoms and the isolation of associated fungi. The survey was conducted at various chili farming locations in South Pesisir District, West Sumatra, Indonesia, to obtain representative samples. Fungal identification was performed using conventional NGS methods. The results of identification using conventional techniques yielded 298 fungal isolates, which were divided into 8 groups based on macroscopic characteristics and 3 genera based on microscopic characteristics, namely Colletotrichum 78.18%, Fusarium 16.11%, and Curvularia 5.7% Meanwhile, the fungi obtained using NGS techniques comprised 10 genera: Colletotrichum 26.36%, Peltula 22.34%, Moniliella 18.73%, Russula 15.2%, Linderina 12.13%, Fusarium 1.13%, Hydnum 0.98%, Rhexocercosporidium 0.44%, Crocinoboletus 0.33%, and Gymnopilus 0.36%, with 198 species. The results of this study indicate that fungal diversity associated with anthracnose symptoms using NGS technology is higher than that identified using conventional methods. These findings regarding dominant pathogenic fungi and their high variability provide important guidance for designing appropriate control measures and optimizing fungicide application.